Identification of monoamine oxidases inhibitory peptides from soybean protein hydrolysate through ultrafiltration purification and in silico studies. (December 2021) - Ying, Fan; Lin, Shiqi; Li, Jingyu; Zhang, Xuewu; Chen, Gu
Abstract: Monoamine oxidases (MAOs, including MAO-A and MAO-B) are essential deamination enzymes for neurotransmitters and other amines; thus, they are potential targets for treatment of mental disorders like depression and anxiety, and neurodegenerative disorders like Alzheimer's disease and Parkinson's disease. This study aimed at identifying MAOs inhibitory peptides from soybean protein hydrolysate through ultrafiltration purification and in silico prediction. Ultrafiltration fraction (0–3 kDa, SP-III) from soybean protein hydrolysate showed the highest inhibition activity with IC50 of 3.211 ± 0.125 mg/ml and 1.622 ± 0.025 mg/ml for MAO-A and MAO-B, respectively. Component 3 from SP-III gel filtration fraction exhibited the highest inhibitory activity with IC50 of 1.623 ± 0.150 mg/ml and 1.174 ± 0.111 mg/ml for MAO-A and MAO-B, respectively. Further affinity purified samples were sequenced by liquid chromatography tandem mass spectrometry and screened by HPEPDOCK. Eight peptides were selected for synthesis and evaluation. YSPYPQ displayed the highest MAO-A inhibitory activity with IC50 of 0.663 ± 0.091 mM, while PLYSN possessed the strongest MAO-B inhibition effect as IC50 of 0.204 ± 0.042 mM. Molecular docking revealed that their binding with MAOs might obstruct admission of substrate to the active sites. Current research confirmed that ultrafiltration purification and in silico prediction are effective to screen MAOs inhibitory peptides from soybean protein hydrolysate. The inhibitor peptides screened out here, especially PLYSN could be applied as potential functional nutraceuticals as MAOs inhibitor to treat neurodegenerative and mental disorders. Their application might suggest value of soybean as a routine and cheap source of neuromodulatory bioactive peptides. Graphical abstract: Image 1 Highlights: Fraction (<3 kDa) of soybean protein hydrolysate strongly inhibit MAO-A and MAO-B. YSPYPQ displayed the highest MAO-A inhibitory activity with IC50 of 0.663 mM. PLYSN possessed the highest MAO-B inhibitory activity with IC50 of 0.204 mM. YSPYPQ interacts with residue in MAO-A substrate binding region in silico analysis. PLYSN interacts with residues in entrance loop of MAO-B in in silico analysis.